2006
DOI: 10.1097/01.ccm.0000229145.04482.93
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of weight and height estimation in an intensive care unit: Implications for clinical practice and research*

Abstract: Individual estimates of weight and height are frequently inaccurate. These errors of estimation could compromise application of effective therapies, as well as contribute to a reduction in design sensitivity of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
81
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 34 publications
8
81
0
1
Order By: Relevance
“…Our results are in agreement with previous data that showed inaccuracy of visual estimations in different populations. [15][16][17][18]31,32 To our knowledge, there is no study evaluating accuracy of the tape measure method in bedridden patients in comparison with the reference method with a height gauge when patients are standing upright. Several methods have been described to obtain a patient's height indirectly, among which lower leg measurement (kneeheel length, Chumlea method), [24][25][26] forearm measurement (from elbow to wrist), and demispan (distance from the middle of the sternal notch to the tip of the middle finger in the coronal plane) are the most frequently evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with previous data that showed inaccuracy of visual estimations in different populations. [15][16][17][18]31,32 To our knowledge, there is no study evaluating accuracy of the tape measure method in bedridden patients in comparison with the reference method with a height gauge when patients are standing upright. Several methods have been described to obtain a patient's height indirectly, among which lower leg measurement (kneeheel length, Chumlea method), [24][25][26] forearm measurement (from elbow to wrist), and demispan (distance from the middle of the sternal notch to the tip of the middle finger in the coronal plane) are the most frequently evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, visual estimation of height and, even more so, of PBW can be inaccurate. [15][16][17][18] In addition, despite strong evidence and recommendations, protective mechanical ventilation is not optimally implemented [19][20][21][22][23] ; unavailability of the height may be an additional barrier. 11 Considering the central role of the physiologic value of the patient's height and its impact on mechanical ventilation settings, we conducted this study to evaluate the accuracy of usual measurements of height in mechanically ventilated patients and to assess alternative measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In a small sample of intensive care unit patients, Bloomfield et al found that 18 of 20 bedside estimates were within 15% of true height and the majority were within 10% (11). No studies, however, have evaluated the ability of health care providers to estimate true height (TH), and by extraction, IBW in a large ED sample of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Weight is more problematic with Hendershot et al (1) reporting significant inaccuracies between patient-reported and relativereported weight. Estimation of weight by experienced healthcare providers has also been shown to be grossly inaccurate (2) .…”
mentioning
confidence: 99%